THE INTEGRAL PROTECTION OF HUMAN RIGHTS DEFENDERS: And the role of Brazilian civil society - de Lima Neto, Antonio Francisco; Tavares, Ana Claudia (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2023)
In a context of increasing violence and violations against human rights defenders, this article seeks to initiate a discussion on the protection of human rights defenders from a integral perspective developed by organized civil society over the past 25 years. The text emphasizes the need to discuss actions and strategies that enable social movements and human rights defenders to operate in a safer and more protected manner. Similarly, we aim to understand the role of social movements and civil society human rights organizations in the protection of these individuals and their communities.